Community-Based Rural Tourism in Super-Ageing Japan: challenges and evolution - Ohe, Yasuo (Anais Brasileiros de Estudos Turísticos, 2016)
Japan became a super-ageing society in 2005, with rural Japan becoming extremely super-aged. This paper investigated how a rural community conducts tourism activity and how it copes with challenges through studying a community-based rural tourism activity in Chiba. By defining community-based rural tourism as using a bonding type of social capital in the local community, this paper explored the advantages and limitations of this type of social capital when the social capital becomes older. Specifically, it was revealed that community-based rural tourism has done well from aspects of job and income generation, increases in self-confidence and local pride, and to a certain extent coping with the impact of unexpected natural disasters. On the other hand, transferring these activities to the younger generation while maintaining the community-based decision-making system will be challenging. Thus, there comes a time when the use of the traditional bonding social capital within the local community must be expanded toward a more open, wider, and new network beyond the local community.